Early Childhood Development in Latin America and the Caribbean - Schady, Norbert (World Bank, Washington, DC, 2012)
There is considerable evidence that young children in many developing countries suffer from profound deficits in nutrition, health, fine and gross motor skills, cognitive development, and socio-emotional development. Early childhood development (ECD) outcomes are important markers of the welfare of children. In addition, the deleterious effects of poor outcomes in early childhood can be long-lasting, affecting school attainment, employment, wages, criminality, and measures of social integration of adults. This paper considers the theoretical case to be made for investments in early childhood, selectively reviews the literature on the impact of ECD programs in the United States, discusses the evidence from Latin America and the Caribbean, and makes suggestions for future research. The focus is on the relation between outcomes in early childhood and measures of household socioeconomic status, child health, and parenting practices, as well as on the impact of specific policies and programs. The knowledge base on early childhood outcomes is still thin in Latin America and the Caribbean. There are therefore very high returns to comparative descriptive analysis in the region, as well as to careful evaluations of the impact of various programs.